Efforts of the French envoy to conclude a separate Polish–Turkish peace in the years 1693–1697 - Skrzypietz, Aleksandra (Balcanica Posnaniensia. Acta et studia, 2003)
Between 1693 and 1697, French diplomacy worked intensively to exclude the Polish-Lithuanian Commonwealth from the war between the Holy League and the Ottoman Empire and to bring about a separate Polish-Turkish peace. The key figure in these efforts was the new French ambassador to Poland, Abbé Bonport, Melchior de Polignac. The young and ambitious diplomat was to influence the Sobieski royal couple and draw Poland to the side of Versailles. The aim of this article is to analyse Polignac's efforts in the context of Louis XIV's foreign policy and to discuss the obstacles he encountered in implementing French plans. Particular attention is paid to the role of Queen Maria Kazimiera, the anti-French opposition at court, and the attitudes of magnates and senators towards the proposal to end the war with Turkey. The source material consists of Polignac's diplomatic dispatches, royal correspondence, contemporary memoirs and literature on the subject. The conclusions indicate that despite repeated attempts, Polignac failed to convince John III or the Polish-Lithuanian political elite to make peace with Turkey. The reason for this was Poland's difficult-to-fulfil territorial expectations (the return of Kamieniec and Podolia). After the death of John III, the ambassador became involved in an attempt to place a French candidate, Prince Conti, on the throne, which also ended in failure. France's actions did not bring the expected results, and peace with Turkey was only concluded under the Treaty of Karlowitz in 1699.